Producción primaria fitoplanctónica de un lago somero turbio orgánico en relación con el zooplancton (La Pampa, Argentina) - Vignatti, A. (2009)
Primary production (PPr) is the energy fixed by autotrophic organisms. In aquatic ecosystems, it is mostly produced by photosynthetic processes performed by planktonic or benthic algae and macrophytes. In La Pampa, the ecology of shallow lakes has recently begun to be studied, but there is no reference inade to the algal PPr and how it is influenced by zooplankton. Since shallow lakes in La Pampa are different from those widely studied in Buenos Aires province, the objective of this contribution was to determine the phytoplanktonic PPr of an organic turbid shallow lake of the northeast La Pampa, and the influence of zooplankton in its valué. PPr was estimated 6 times along the day with the dissolved oxygen technique, using clear and dark bottles. To test the ef- fect of zooplankton on PPr estimates, we compared PPr with and without zooplankton, which was removed with a 40-micron mesh net. A higher concentration of nutrients was recorded than the typical pampasic shallow lakes of Buenos Aires province, Phytoplank- ton was dominated by Chlorophyta and the zooplankton assemblage was typical of low salinity environments. Zooplankton densities were reduced during noon-afternoon hours, what might indícate an important zooplankton migration process. Net PPr was similar to the detected in lakes at similar latitudinal location, but the máximum PPr per unít chlorophyll was higher than the recorded in organic turbid lakes of Buenos Aires Province. Zooplankton had a weak influence on PPr. Determinations from the two treat- ments did not show significant differences, except at 8 PM when the net PPr without zooplankton was three times higher than the treaíment with zooplankton.